Cross-sectional investigation of quality of life determinants among children with tic disorders: The roles of family environmental and clinical factors. Issue 2 (February 2023) - Liu, Fang; Wang, Gaohua; Yao, Baozhen; Ye, Jingping; Wang, Junling; Wang, Huaqian; Liu, Hong
Abstract: Objective: To examine the association between family environmental and clinical factors with the whole range of quality of life (QOL) in children with tic disorders (TD). Methods: A hospital-based cross-sectional study was conducted among children with TD. All participants were given a family environmental survey and scale evaluations with Yale Global Tic Severity Scale (YGTSS), Achenbach Child Behavior Checklist (CBCL) and PedsQL-Generic Core Scale of the Chinese Version (PedsQL). Variable selection and data analysis was done by the least absolute shrinkage and selection operator (LASSO) method and multivariate logistic regression analysis. Results: A total of 363 TD cases were included in the analysis. YGTSS scores, total CBCL score had significant negative correlations with PedsQL scores ( P  < 0.05). Of the total 15 factors, 8, 6, 11, 7, 5, 10 potential predictors with nonzero coefficients were identified by LASSO regression models of physical functioning, emotional functioning, social functioning, school functioning, social-psychological domain and PedsQL total scale respectively. Results of multivariate logistic regression analysis showed older age (physical functioning, ORs: 1.77, 3.67; total scale: ORs: 1.73, 2.28), no presence of chronic conditions (school functioning, OR: 1.61), moderate/severe tic severity (physical functioning, OR: 0.57; social functioning, OR: 0.44; social-psychological domain, OR: 0.57), co-morbid behavioral problems (physical functioning, OR: 0.52; emotional functioning, OR: 0.31; social functioning, OR: 0.30; school functioning, OR: 0.35; social-psychological domain, OR: 0.34; total scale, OR: 0.30), no fully parental involvement in care (physical functioning, OR: 0.62), higher paternal (physical functioning, ORs: 2.89, 2.07) and maternal education level (social functioning, ORs: 1.74, 2.03), democratic parenting pattern (emotional functioning, OR: 1.89; social functioning, OR: 2.17; social-psychological domain, OR: 2.33; total scale, OR: 2.11) and inharmony family relationship (emotional functioning, OR: 0.47; total scale, OR: 0.50) were the most important determinants to QOL of TD. Conclusions: This study identifies several QOL determinants among children with TD. Clinicians should be encouraged to screen for family environmental and clinical factors in TD patients, and take tailored interventions to help TD children improve their QOL.